HOW TO SHARE PROFITS IN COMMUNITY INTEREST FOR INVESTING IN SHARIA ECONOMIC STUDIES. - Ulfatul Khasanah, Ayu Maretta Maharani (STAI AL-HIDAYAT Lasem, 2023)
At that time, Indonesia was on the verge of economic collapse, almost all economic sectors experienced negative growth. Where the construction sector is the sector that experienced the largest negative growth, which is minus 40% due to very high interest rates, declining purchasing power, and a very large debt burden. The trade and services sector experienced a contraction of minus 21%, the manufacturing industry sector decreased by 19%. All of this resulted from the implications of the monetary crisis that rocked Indonesia. This is because people's purchasing power is still minimal. Therefore, one of the efforts to revive the economy is by means of profit sharing. The profit sharing system applied in Islamic banking is divided into two systems, namely; first. Profit Sharing, which is a profit sharing system based on the net results of income received from business cooperation, after deductions for cost burdens during the business process.